Grammar and Formulaicity in Foreign Language Teaching - Gozdawa-Gołębiowski, Romuald (Wydawnictwo Naukowe UAM, 2008)
There are three general problem areas in the production of native-like language by the foreign learner: lexically based co-occurrence restrictions, inflectional paradigms and function words with little semantic impact. Remedial action can either be rule-based or dictionary-based. This corresponds to two traditionally recognized modes of sentence processing: analytic (with conscious reference to the grammatical system) or holistic (formulaic, where whole chunks are attended to). I argue for the existence of a third, middle-of-the-road strategy, which I tentatively label the "contentive" mode of sentence processing, with the focus on content-bearing individual lexical items.. Contentive processing is a key factor in the modular concept of formulaicity, proposed in this paper. A formula can be thought of as a bundle of opaque features, a recurrent unit, a social token or a morphosyntactic exemplar. This puts a different perspective on language teaching.
Keywords: Grammar; Foreign Language Teaching